Manual of regulations for private schools annotated - Sarmiento, Ulpiano Planes; Cruz, Cynthia L. (Quezon City Risen Publishing, 1995)
An annotation of the different legislation regarding private schools.
"This 802 pages Manual of Regulations of Private Schools was issued by DECS on August 10, 1992 through DECS order No. 92, series of 1992, pursuant to the pertinent provisions of the 1987 Constitution, Act No. 2706 as amended by Act No. 3075, Commonwealth Act No. 180, Batas Pambansa Blg. 232 and other applicable legislation. The manual consists of 18 articles that are divided into six major sections focusing on the deregulation of private schemes. A significant feature of the new manual is its emphasis on accreditations as stimulus for and a measure of institutional scholastic improvements."
Keywords: Education -- Philippines; Private schools -- Philippines -- Handbooks, manuals, etc